The Digital Game for Curriculum Public Relations (PR) and Learning Using Unity3D - Puttinaovarat, Supattra; Pruitikanee, Siwipa; Kongcharoen, Jinda; Saeliw, Aekarat; Inthong, Ponkrint; Thippayamongkol , Nanthachot (International Journal of Interactive Mobile Technologies (iJIM), 2023)
In the age of digital disruption, universities and educational institutions all over the world provide many bachelor’s, postgraduate, and non-degree curriculums. Information is mostly presented in different forms, i.e., PR on websites, mobile applications, or social media; including field PR at different sites, e.g., department stores and schools. However, the limitations and the problems are that presented information fails to attract or motivate perception, interest, and participation of the target groups. Also, traditional PR requires resources in terms of persons, time, and a large amount of expenditures. Thus, this research aimed to present the development of a game to present information for PR of bachelor’s curriculums using Unity3D, which could reduce the limitation of presentation or PR in the traditional forms. It could also save PR budget and could be done anywhere and anytime.